The environment and emmerging development issues; T2 (Oxford, 1998)
In these two volumes, expert contributors provide a set of authoritative studies of emerging development issues, ranging from foundational matters to case studies. They address both analytic and emprical issues on the role of environmental resources in the development process, presenting explanations of existing situations and policies for the future. Their chapters go beyond the confines of environmental economics proper to cover broader theoretical issues fundamental to our understanding of environmental policy.
Keywords: economic development projects